My creature teacher - Leuck, Laura; Nash, Scott, 1959- (New York : HarperCollins, 2004)
A student describes all the things that his creature teacher does at school.
Keywords: Teachers -- Fiction; Monsters -- Fiction; Schools -- Fiction; Stories in rhyme